The given expression is :
![0=x^2+3x-10](https://img.qammunity.org/2023/formulas/mathematics/college/fsfsdow0ymbnshtuih90e4ywpqfokfkct8.png)
Factorize the expression :
![\begin{gathered} 0=x^2+3x-10 \\ x^2+3x-10=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kg8ke06iay0qg617ym9wxsp6qhgthtwx6i.png)
Find the pair of number such that : the product of two numbers are equal = (-10)
and thier summation is equal to 3
i.e. 5 x ( -2) = -10 and 5 + (-2) = 3
So,
![\begin{gathered} x^2+3x-10=0 \\ x^2+5x-2x-10=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6owimat9fhzjzkg0tmnxsi02vgqy6hsem4.png)
Take x common from the first two terms and (-2) from last two terms :
![\begin{gathered} x^2+5x-2x-10=0 \\ x(x+5)-2(x+5)=0 \\ \text{Now, take (x+5) common :} \\ (x-2)(x+5)\text{ =0} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j3epkjhva4hjxpiha0in66sjzfsmr6fqy9.png)
Now equate each factor with zero :
![\begin{gathered} (x-2)(x+5)=0 \\ x-2=0\Rightarrow x=2 \\ x+5=0\Rightarrow x=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w9jzokamg4cy9ncyo3np9mvox66b5f5lxv.png)
Answer : C) x = -5, 2